Loss of Dickkopf-1 restores neurogenesis in old age and counteracts cognitive decline - Seib, Désirée Rosa Maria; Corsini, Nina S.; Ellwanger, Kristina; Plaas, Christian; Mateos, Alvaro; Pitzer, Claudia; Niehrs, Christof; Celikel, Tansu; Martín-Villalba, Ana (Cell stem cell, 2013)
Memory impairment has been associated with age-related decline in adult hippocampal neurogenesis. Although Notch, bone morphogenetic protein, and Wnt signaling pathways are known to regulate multiple aspects of adult neural stem cell function, the molecular basis of declining neurogenesis in the aging hippocampus remains unknown. Here, we show that expression of the Wnt antagonist Dickkopf-1 (Dkk1) increases with age and that its loss enhances neurogenesis in the hippocampus. Neural progenitors with inducible loss of Dkk1 increase their Wnt activity, which leads to enhanced self-renewal and increased generation of immature neurons. This Wnt-expanded progeny subsequently matures into glutamatergic granule neurons with increased dendritic complexity. As a result, mice deficient in Dkk1 exhibit enhanced spatial working memory and memory consolidation and also show improvements in affective behavior. Taken together, our findings show that upregulating Wnt signaling by reducing Dkk1 expression can counteract age-related decrease in neurogenesis and its associated cognitive decline.